Salivary Biomarkers: Future Approaches for Early Diagnosis of Neurodegenerative Diseases - Giovanni Schepici; Serena Silvestro; Oriana Trubiani; Placido Bramanti; Emanuela Mazzon (Brain Sciences, 2020)
Many neurological diseases are characterized by progressive neuronal degeneration. Early diagnosis and new markers are necessary for prompt therapeutic intervention. Several studies have aimed to identify biomarkers in different biological liquids. Furthermore, it is being considered whether saliva could be a potential biological sample for the investigation of neurodegenerative diseases. This work aims to provide an overview of the literature concerning biomarkers identified in saliva for the diagnosis of neurodegenerative diseases such as Alzheimer’s disease (AD), Parkinson’s disease (PD), amyotrophic lateral sclerosis (ALS), and multiple sclerosis (MS). Specifically, the studies have revealed that is possible to quantify beta-amyloid1–42 and TAU protein from the saliva of AD patients. Instead, alpha-synuclein and protein deglycase (DJ-1) have been identified as new potential salivary biomarkers for the diagnosis of PD. Nevertheless, future studies will be needed to validate these salivary biomarkers in the diagnosis of neurological diseases.